Application of pressure-sensitive paint for the characterization of mixing with various gases in T-type micromixers. (August 2020) - Huang, Chih-Yung; Hu, Yu-Hsiang; Wan, Shaw-An; Nagai, Hiroki
Highlights: Pressure-sensitive paint technique was applied to visualize and quantify the mixing of various gases with oxygen. The effects of the density, dynamic viscosity, and diffusion coefficient on mixing were discussed with detailed mixing quality evolution inside mixing channel. Numerical simulation have been performed with favorable agreement with experimental data. Engulfment and laminar flow patterns changed with different gas mixing and identified by pressure-sensitive paint experiments. Abstract: In this study, the mixing of various gases in T-type micromixers was investigated using the pressure-sensitive paint technique. Three gases, namely nitrogen, argon, and helium, were mixed with oxygen at various flow speeds between 3 and 50 m/s. These three gases were selected because of their differences in terms of density, viscosity, and diffusion coefficients. Symmetric flow in the laminar flow regime and bifurcation flow in the engulfment flow regime were visualized through experimentation. Numerical simulation was also performed, and the numerical data were compared with the experimental data. A favorable agreement was obtained between the experimental and numerical results for the laminar flow regime. The effects of the properties of the mixed gases as well as the evolution of the mixing quality along the mixing channel in the T-type micromixer are discussed.